Mengenal Religi Para Bapak Leluhur Israel - Noh Ibrahim Boiliu; Irfan Feriando Simanjuntak (Sekolah Tinggi Teologi Real Batam, 2019)
This paper aims to describe the religion of the Israelite ancestors. The problem discussed in this paper is which God the Israelite ancestors worshiped. The approach is to analyze several sources of the Old Testament relating to Israelite religion. Even though the three Semitic religions of Judaism, Christianity and Islam worship the same God